Notice that if you open the brackets yields:
You need to have all terms to one side such that:
You should use quadratic formula such that:
Identifying a,b,c yields: a=1, b=-2, c=0
Hence, evaluating the zeroes to quadratic equation yields and .
It is a quadratic and you can solve accordingly.
But there is another manner to approach the problem, without using quadratic formula.
We'll move the term from the right side, to the left side, because it is a term in x.
x(x-7) + 5x = 0
We can factorize by x:
x(x - 7 + 5) = 0
We'll combine like terms inside brackets:
x(x - 2) = 0
A product of 2 factors is zero if one of them is zero:
x = 0
x - 2 = 0
The solutions of the equations are 0 and 2.